Allograft to bone-tunnel integration in a canine anterior cruciate ligament reconstruction model: a comparison study of allograft preparation methods - Xiaoke Shang; Jianzhong Hu; Jin Qu; Peng Wen; Jian Li; Qi Li; Jun Zheng (Journal of Orthopaedic Surgery and Research, 2024)
Abstract The procedure of anterior cruciate ligament (ACL) allograft preparation can be divided into fresh-frozen method (FF-allograft) or freeze-dried method (FD-allograft). This study aims to biomechanically and histologically compare the graft to bone tunnel integration between the two allografts. In-vitro results indicated that FF-allograft and FD-allograft showed excellent biocompatibility and biomechanics, while FD-allograft showed a denser collagen fiber arrangement than FF-allograft and autograft. Then, in-vivo preformation of the FF-allograft, FD-allograft, and autograft on bone tunnel integration was evaluated via a canine ACL reconstruction model. In-vivo results indicated that no signs of infection or osteoarthritis were shown in the femur-graft-tibia complexes, but more vascularity and synovitis formed around the implanted FF-allograft. Micro-computed tomography showed that peri-graft bone in the FF-allograft group was significantly increased and remodeled compared with the FD-allograft group; Histologically, the FF-allograft group exhibited similar graft-bone tunnel healing to the FD-allograft group. Tartrate-resistant acid phosphatase (TRAP) staining showed significantly more osteoclasts presented in the FD-allograft group compared to the FF-allograft group. Meanwhile, a significantly higher failure load was shown in the FF-allograft group when compared with the FD-allograft group (P < 0.05). In conclusion, the FF-allograft integrated more firmly into the bone tunnel than the FD-allograft when used in ACL reconstruction.